Molecular Characteristics of Regional Chromoblastomycosis in Guangdong, China: Epidemiological, Clinical, Antifungal Susceptibility, and Serum Cytokine Profiles of 45 Cases - Liu, Hongfang; Sun, Jiufeng; Li, Minying; Cai, Wenying; Chen, Yangxia; Liu, Yinghui; Huang, Huan; Xie, Zhenmou; Zeng, Weiying; Xi, Liyan (Frontiers in Cellular and Infection Microbiology, 2022)
Chromoblastomycosis (CBM) is a chronic disease caused by several species of dematiaceous fungi. In this study, a regional collection of 45 CBM cases was conducted in Guangdong, China, a hyper-endemic area of CBM. Epidemiology findings indicated that the mean age of cases was 61.38 ± 11.20 years, long duration ranged from 3 months to 30 years, and the gender ratio of male to female was 4.6:1. Thirteen cases (29%) declared underlying diseases. Verrucous form was the most common clinical manifestation (n = 19, 42%). Forty-five corresponding clinical strains were isolated, and 28 of them (62%) were identified as F. monophora; the remaining 17 (38%) were identified as F. nubica through ITS rDNA sequence analysis. Antifungal susceptibility tests in vitro showed low MICs in azoles (PCZ 0.015–0.25 μg/ml, VCZ 0.015–0.5 μg/ml, and ITZ 0.03–0.5 μg/ml) and TRB (0.015–1 μg/ml). Itraconazole combined with terbinafine was the main therapeutic strategy used for 31 of 45 cases, and 68% (n = 21) of them improved or were cured. Cytokine profile assays indicated upregulation of IL-4, IL-7, IL-15, IL-11, and IL-17, while downregulation of IL-1RA, MIP-1β, IL-8, and IL-16 compared to healthy donors (p < 0.05). The abnormal cytokine profiles indicated impaired immune response to eliminate fungus in CBM cases, which probably contributed to the chronic duration of this disease. In conclusion, we investigated the molecular epidemiological, clinical, and laboratory characteristics of CBM in Guangdong, China, which may assist further clinical therapy, as well as fundamental pathogenesis studies of CBM.